The Combination of Berberine and Methotrexate Enhances Anti-Cancer Effects in Hela Cancer Cell Line: A Morphological Study - Hossein Majidzadeh; Mostafa Araj-Khodaei; Maryam Ghaffari; Amir Jafari; Dariush Shanehbandi; Mohammadali Torbati; Jafar Ezzati Nazhad Dolatabadi (Tabriz University of Medical Sciences, 2021)
Background: Co-administration of two or several either chemotherapeutic agents or conventional drugs as a combination treatment is the most effective method to increase therapeutic efficiency. Additive or synergistic influence are two mechanisms by which combination therapy causes a rise in optimal cancer therapy compared to a single treatment. Methods: Colorimetric assay was carried out to estimate the cytotoxicity of the combined system, followed by apoptosis assay to calculate the number of apoptotic cells. Both 4',6-diamidino-2-phenylindole (DAPI) staining and DNA ladder were complemented tests to illuminate morphological changes and DNA fracturing on HeLa cancer cells. Results: We revealed that the combination of berberine (BER) and methotrexate (MTX) could inhibit the growth of HeLa cancer cells noticeably. Nevertheless, single BER and MTX were not as effective as a combined system to reduce cell viability at the same dose. Regarding the apoptosis induction and change in morphology of cancer cells' nucleus, co-treatment of BERand MTX was more effective. The result was complemented with flow cytometry, DAPI staining and DNA ladder, which showed that BER+MTX depicted more anti-cancer effects. Conclusion: The combination therapy of HeLa cancer cells with BER and MTX showed high inhibition effect compared to other treated groups.